Levels of linear alkylbenzene sulfonates and nonylphenol in wild bat guano samples - Gonkowski, Slawomir; Martín, Julia; Aparicio, Irene; Santos, Juan Luis; Alonso, Esteban; Sowinska, Wioleta; Rytel, Liliana (Frontiers in Environmental Science, 2025)
IntroductionSurfactants are substances that are commonly used in the industry, and they pollute the environment and negatively affect living organisms. In this article, we describe, for the first time, the exposure of wild bats to selected surfactants: nonylphenol (NP) and linear alkylbenzene sulfonates (LASs), including LAS C10, LAS C11, LAS C12, and LAS C13 (where “C” with a number indicates the length of the alkyl carbon chain).MethodsThe levels of the abovementioned compounds were evaluated in guano samples collected from various colonies of the greater mouse-eared bat (Myotis myotis) using liquid chromatography coupled with mass spectrometry (LC-MS/MS).Results: All surfactants studied were found in the guano samples. Mean levels of LASs (±SD) ranged from 87 ± 28.5 ng/g (median 75.1 ng/g) in the case of LAS C10 to 662 ± 227.2 ng/g (median 560.5 ng/g) in the case of LAS C12. The mean concentration of NP was 65.2 ± 74.9 ng/g (median 23.5 ng/g). Moreover, significant differences in surfactant levels were noted between particular bat colonies.DiscussionThe results showed that wild bats are highly exposed to LASs and NP, and the degree of this exposure shows clear intraregional differences. Moreover, the study demonstrated that guano samples serve as a valuable tool to assess bat exposure to these surfactants.